PENGARUH SARANA DAN PRASARANA PEMBELAJARAN TERHADAP PENINGKATAN MOTIVASI BELAJAR DI TK CEMPAKA DESA PANTAI LABU PEKAN - Fakhrana, Ayu; Nasution, Ummi Hani; Dary DN, Widia Ulan; Nasution, Candri Wulan; Priyanti, Dhea; Delvia, Elyca; Hariyanti, Hariyanti; Hikmah, Ikmalul; Azzahra, Khadijah (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this study was to determine whether the facilities and resources available at Cempaka Kindergarten in Pantai Labu Pekan village influenced students' learning motivation. The type of research used in this research is the descriptive qualitative method, namely the researcher tries to reveal a fact or reality of certain social phenomena as they are. Which aims to determine the effect of school facilities and infrastructure on increasing learning motivation in Kindergarten Cempaka, Pantai Labu Pekan village. The experimental unit in this study was all 30 students. The research was carried out in 6 meetings. The benchmark in this study is the availability of standard educational facilities and infrastructure including study rooms, sports areas, places of worship, libraries, laboratories, workshops, playgrounds, recreation and creative areas, and other learning resources needed to support the learning process. including the use of information and communication technology. The results of testing the hypothesis show that the r value obtained from the calculation (r-count) = 0.484 is greater than the r value obtained from the distribution table r (r-table) r-table = 0.361 with a significance level of 5% (r-count > r-table). The meaning shows that H1 is accepted. This proves that school facilities and infrastructure influence increasing student learning motivation in Cempaka kindergarten, Pantai Labu Pekan village.